Desempenho zootécnico do peixe panga (Pangasianodon hypophthalmus) alimentado com ração enriquecida a base de farinha de Spirulina sp. - Pavão, Paulo Ricardo de Oliveira (Universidade Federal Rural do Semi-Árido, 2020)
The present work aims to verify the zootechnical performance of Pnagasianodon hypophthaulmus fed with commercial tilapia food enriched with Spirulina sp. Flour. Altogether there were 5 treatments, the control without flour of Spirulina sp. and the others in increments of 5, 10, 15 and 20% of the flour. The final biomass, final average weight, survival and FCAA data were subjected to one-way ANOVA analysis of variance. If significant differences were detected between treatments, the Tukey test was applied at 5% significance level (P <0.05. There were no significant differences between the treatments performed, possibly due to stressful conditions, caused by the adopted form of aeration. individual average weight and final biomass were for with 13.4 g and 400 kg.ha-1, respectively, the average value for FCAA was 11.2 / 1 and the average for the survivals was 90%. it can be concluded that in the culture situations in which this experiment was carried out, Spirulina sp did not present zootechnical gains for the Pnagasianodon hypophthalmus.
Monografia
Keywords: Nutriçao; Peixe; Pangasius; Spirulina sp.; Fish; Nutrition; Pangasius; Spirulina; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA